Characteristics of hypertension and its impact on cognitive functions in older adults: a cross-sectional study - Parandiyal, Nivedita; Chutia, Porimita; Sinha, Shashank Saurabh; Pandit, Pratyaksha; Majrashi, Naif Ali; Qureshi, Naseem; Tripathi, Shailendra Mohan (Frontiers in Dementia, 2024)
Background: Hypertension is a potentially modifiable risk factor for cognitive decline.Understanding the variables of hypertension related to cognitive functions will help in mitigating the risk.The study aims to assess the characteristics of hypertension and its effect on cognitive functions in the older adults.The study involved 95 hypertensive participants aged 60 years and above from cardiology and medicine outpatient services of a tertiary care hospital from August to October 2022. The characteristics of hypertension and cognitive functions were assessed using semistructured proforma and Adenbrooke's Cognitive Examination (ACE-III) Hindi version respectively. Further, individual cognitive functions were compared with duration of the hypertension and hypertensive status of the participants. The chi-square test and independent ttests were used and p value < 0.05 was considered to be significant.The mean age of the study population was 68.2 years, the cognitive functions was comparable in terms of age, sex, locality, co-morbidity, and treatment characteristic. Although a significant difference in cognitive functions was present in relation to duration and status of hypertension. Among the individual cognitive domains, a significant difference was observed in attention and fluency domains of cognitive function based on HTN status (p > 0.05) but differential effect on cognitive domains was not seen with the duration of HTN. However, there was overall decline in cognitive domains with both hypertension status and the duration of hypertension.The study highlights association of status of hypertension and its characteristics with cognitive decline.